SERS active surface in two steps, patterning and metallization - Acevedo, Diego Fernando (2012)
Robust and reproducible metallized nano/microstructured surfaces of polymeric surfaces have been successfully prepared by direct laser interference patterning (DLIP) of commercial polymeric films followed by sputtering of metallic thin films. The SERS spectra for 2-thioaniline adsorbed on a structured polycarbonate surfaces covered with a gold or platinum film showed a ca. three order of magnitude enhancement over a flat surface with the same metal film. The method here reported is suitable for mass production of substrates for SERS since large areas (several cm2 ) can be structured in ca. 1–5 s.